2012
DOI: 10.3892/or.2012.2131
|View full text |Cite
|
Sign up to set email alerts
|

Ophiopogonin B-induced autophagy in non-small cell lung cancer cells via inhibition of the PI3K/Akt signaling pathway

Abstract: Ophiopogonin B (OP-B) is a bioactive component of Radix Ophiopogon Japonicus, which is often used in Chinese traditional medicine to treat pulmonary disease. However, whether or not OP-B has any potential antitumor activity has not been reported. Here, we show that the non-small cell lung cancer (NSCLC) cell lines NCI-H157 and NCI-H460 treated with OP-B grow more slowly and accumulate vacuoles in their cytoplasm compared to untreated control cells. Flow cytometric analysis showed that the cells were arrested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 21 publications
1
48
0
Order By: Relevance
“…Radix Ophiopogon japonicus is an important medicinal herb widely used for the treatment of various tumors, inflammatory diseases, hepatitis and diarrhea in East Asian countries, including China, Korea, Taiwan, and Japan (18)(19)(20)(21). The plant has been reported to contain a large number of steroidal saponins.…”
Section: Introductionmentioning
confidence: 99%
“…Radix Ophiopogon japonicus is an important medicinal herb widely used for the treatment of various tumors, inflammatory diseases, hepatitis and diarrhea in East Asian countries, including China, Korea, Taiwan, and Japan (18)(19)(20)(21). The plant has been reported to contain a large number of steroidal saponins.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been reported that the overexpression or restoration of miR-135a represses proliferation and facilitates apoptosis of tumor cells by its target genes c-Myc in renal cell carcinoma [16], JAK2 in lymphoma [17], and ROCK1 in gastric cancer [18]. We find that the PI3K/Akt signaling pathway is commonly investigated for its promotion of NSCLC progression in vivo and in vitro as the underlying mechanism of miR-135a in NSCLC [19, 20]. Interestingly, the findings of Ma et al and Salani et al provoked us to speculate that the IGF-1/PI3K/Akt signaling pathway may play an important role in NSCLC [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…In human NSCLC cell lines NCI-H157 and NCI-H460, OP-B was proved to induce autophage of cancer cells via inhibition of the PI3K/Akt signaling pathway (90).…”
Section: Saponinmentioning
confidence: 99%